A systematic approach for closer integration of cellular and Internet services. - Gurbani, V.K.
The road to 4G runs through 3G, 2G and 2.5G networks. Until 3G is deployed ubiquitously, 2-2.5G networks and endpoints dominate. Because of their widespread deployment and adoption, these endpoints can help ease the transition to an all-Internet 3G/4G network. We describe a standards-based service architecture and its implementation that allows 2-2.5G endpoints to participate as active actors in realizing Internet services like presence and instant messaging without the endpoints themselves being connected to the Internet. Our architecture also demonstrates service migration, wherein a successful 2G service such as short messaging service morphs transparently into its Internet equivalent, an instant message. Our methodology conserves precious radio access bandwidth by offloading such data services from the bandwidth normally allocated to voice. Our approach, as embodied in the service architecture, is to leverage the best of the Internet protocols (SIP, XML) and technologies (instant messaging, presence) to provide a general framework for personalized service specification and execution.
Keywords: 2.5G network; 2G network; 3G network; 4G network; Internet protocol; Internet service; Cellular service; Radio access bandwidth